Multiculturalism in Malaysian short stories written in English (1966-2009) - Mohd Ramli, Aimillia (2009)
While it is officially accepted as a main feature of Malaysian society, multiculturalism’s ideological aims of recognizing, celebrating and maintaining cultural identities in order to promote and encourage social cohesion and unity have, nonetheless, often been limited by resistance against extending equitable status to the distinct cultural, religious and ethnic groups within the country. This paper traces the tension between the promotion of national unity and calls for equal status within the multicultural context of Malaysian short stories in English. The importance of literature as a mode for discussing and expressing this tension can never be underestimated. This is because outright discussions on calls for equal status for all of Malaysian cultures have never been officially welcomed by the government since they were deemed “sensitive issues.” Only through literary works, such as short stories, which often appear to be apolitical, are writers able to articulate and discuss issues surrounding multiculturalism, including those of cultural equality, more freely. Because of the evolving nature of any society and the different historical specificities that it experiences, this paper chooses to focus on the treatment of multiculturalism within the Malaysian context in ten short stories over half a century, dating from the sixties until today. Within this time period, this study has managed to locate shifts in the development of this issue from earlier representations of the various interethnic problems in Malaysia to more current emphasis on nationalism and globalization.